Absorption and Desorption Behaviour of the Flavonoids from Rubus chingii Hu Fruit on Macroporous Adsorption Resins - Qian Chen (Science Faculty of Chiang Mai University, 2019)
The kinetics of adsorption and desorption behaviours of ADS-17, DM-301 and S-8 macroporous resins for enriching flavonoids from Rubus chingii Hu fruit were investigated. S-8 resin exhibited stronger adsorption capacity due to chemical and physical properties. The pseudo-second-order kinetics model was the most favorable for illustrating the whole exothermic adsorption process of S-8 resin, which was affected by the mutual effects of boundary layer diffusion and intraparticle diffusion kinetics. Further column chromatography of S-8 resin showed that the total flavonoids (from 15.03 % to 45.64 %) and tiliroside (from 2.04 % to 9.78 %) were enriched in 50 % ethanol fraction. Meanwhile, the antioxidant capacity was higher than that of the crude extract. The fractions with high flavonoids and tiliroside contents could be used as biologically active ingredients in functional food.